Simultaneous total occlusion of two coronary arteries associated with use of drospirenone-ethinyl estradiol (oral contraceptive) - Hüsnü Atmaca; Diyar Köprülü; Tuncay Kiriş; Gönül Zeren; İrfan Şahin (Türk Kardiyoloji Derneği Arşivi, 2018)
Although the use of oral contraceptives is associated with an increased risk of venous thromboembolic disease, the risk of myocardial infarction (MI) is unclear. A new, third-generation contraceptive agent, drospirenone-ethinyl estradiol, which contains less estrogen and a new progestogen, drospirenone, in a different combination, has been considered more reliable in terms of risk of MI. However, there have been some cases of MI associated with the use of drospirenone-ethinyl estradiol, despite the protective effects of this oral contraceptive. In this report, a 33-year-old woman who had used drospirenone-ethinyl estradiol for 6 months was admitted with MI and symptoms of cardiogenic shock. Coronary angiography revealed the total occlusion of 2 coronary arteries and so percutaneous coronary intervention was performed. To the best of our knowledge, this is the first case report of simultaneous total occlusion of 2 coronary arteries associated with the use of drospirenone-ethinyl estradiol in the English-language medical literature.